2015
DOI: 10.1186/s12913-015-0959-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients treated with first-line antiretroviral therapy containing nevirapine or efavirenz in Uganda: a prospective non-randomized study

Abstract: BackgroundThe goal of antiretroviral therapy (ART) is to suppress viral replication, reduce morbidity and mortality, and improve quality of life (QoL). For resource-limited settings, the World Health Organization recommends a first-line regimen of two-nucleoside reverse-transcriptase inhibitors and one non-nucleoside transcriptase inhibitor (nevirapine (NVP) or efavirenz (EFV)). There are few data comparing the QoL impact of NVP versus EFV. This study assessed the change in QoL and factors associated with QoL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Nevirapine-based regimen was significantly associated with virological and immunological failure compared to those children who were on EFV-based treatment (AOR = 1:90, (1.41-2.56), P = 0:001) or which is 2 times higher in virological and immunological failure than EFVbased treatment. Consistent findings were reported from Tanzania (AOR = 4:1, (1.6-10.4), P = 0:003) [39], Uganda [41], and Bahir Dar, Ethiopia (AOR = 1:90, 95% CI: 1.41-2.56, P = 0:001) [24]. Contrasting finding from our study was reported from Asella, Ethiopia [42] that indicated HAART regimen variability was not significantly associated Journal of Immunology Research with recovery of CD4 counts and viral load failure, Addis Ababa, Ethiopia [43] and in Uganda study [44].…”
Section: Discussionsupporting
confidence: 86%
“…Nevirapine-based regimen was significantly associated with virological and immunological failure compared to those children who were on EFV-based treatment (AOR = 1:90, (1.41-2.56), P = 0:001) or which is 2 times higher in virological and immunological failure than EFVbased treatment. Consistent findings were reported from Tanzania (AOR = 4:1, (1.6-10.4), P = 0:003) [39], Uganda [41], and Bahir Dar, Ethiopia (AOR = 1:90, 95% CI: 1.41-2.56, P = 0:001) [24]. Contrasting finding from our study was reported from Asella, Ethiopia [42] that indicated HAART regimen variability was not significantly associated Journal of Immunology Research with recovery of CD4 counts and viral load failure, Addis Ababa, Ethiopia [43] and in Uganda study [44].…”
Section: Discussionsupporting
confidence: 86%
“…This study found that Zidovudine and Nevirapin based regimen was significantly more toxic than Tenofovir and Efaverinz based regimens. This finding was supported by a study done in Uganda in 2013 in which ART related ADRs was higher in Nevirapin containing regimen compared to Efaverinz and also study in Ethiopia at Hiwot Fana hospital, in which TDF based regimens was less toxic compared to AZT containing regimens [ 29 , 45 ].…”
Section: Discussionmentioning
confidence: 63%
“…This recommendation is informed by a growing body of evidence that highlights the benefits of early ART initiation [ 2 4 ], including reduced mortality [ 5 ] and morbidity among HIV-infected individuals [ 1 , 6 ]. Expanding access to ART in resource-limited settings over the last two decades has transformed the disease to a manageable chronic illness [ 7 , 8 ] and allows HIV-infected individuals an improved overall quality of life [ 9 ] in these settings. Additionally, a study conducted in Uganda demonstrates that HIV-infected individuals now have similar life expectancy to the general population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%